2017
DOI: 10.3906/sag-1602-60
|View full text |Cite
|
Sign up to set email alerts
|

Meloxicam and diclofenac do not change VEGF and PDGF-ABserum levels of platelet-rich plasma

Abstract: Background/aim: Platelet-rich plasma (PRP) application has gained widespread interest for musculoskeletal injuries. Nonsteroidal antiinflammatory drugs are frequently used in sports medicine before and/or after PRP application. Our study seeks to determine whether serum levels of platelet-derived growth factor-AB (PDGF-AB) and vascular endothelial growth factor (VEGF) levels of PRP would be affected by nonsteroidal antiinflammatory drugs.Materials and methods: Two different final concentrations of diclofenac (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The investigators found no differences in levels of growth factors in the experimental groups compared with in controls. 70 Further evidence to support the lack of effect of cyclooxygenase (COX) 2 inhibition on PRP protein release came from a study in dogs. Ludwig et al 40 showed no statistically significant decreases in TFG-β1, PDGF-BB, or thromboxane B2 release in PRP in dogs given carprofen compared with in controls when activated in vitro via human-γ-thrombin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators found no differences in levels of growth factors in the experimental groups compared with in controls. 70 Further evidence to support the lack of effect of cyclooxygenase (COX) 2 inhibition on PRP protein release came from a study in dogs. Ludwig et al 40 showed no statistically significant decreases in TFG-β1, PDGF-BB, or thromboxane B2 release in PRP in dogs given carprofen compared with in controls when activated in vitro via human-γ-thrombin.…”
Section: Resultsmentioning
confidence: 99%
“…The investigators found no differences in levels of growth factors in the experimental groups compared with in controls. 70 Further evidence to support the Mixed effect a AA, arachidonic acid; ADP, adenosine diphosphate; ASA, aspirin; COX-2, cyclooxygenase 2; FGF, basic fibroblast growth factor; GDF-11, growth differentiation factor 11; HGF, hepatocyte growth factor; IGF-1, insulin-like growth factor 1; IL, interleukin; LR, leukocyte-rich; NSAID, nonsteroidal anti-inflammatory drug; PDGF, platelet-derived growth factor; PRGF, platelet-rich growth factor; PRP, platelet-rich plasma; PRPP, platelet-rich plasma product; TGF-b1, transforming growth factor b-1; TNF-a, tumor necrosis factor a; TRAP-6, thrombin receptor-activated protein 6; TXB2, thromboxane B2; VEGF, vascular endothelial growth factor. The term anabolic factors means that studies attempted to measure growth factors, inflammatory cytokines, and other molecules believed to stimulate platelet activation and wound healing.…”
Section: In Vitro Analysesmentioning
confidence: 99%
“…In vivo studies showed that PRP may have an anti-inflammatory effect by inhibiting the NF-KB pathway. (Utku et al, 2017) Each millilitre of PRP solution contains 1.5-2 million platelets, which represents a 5-fold increase in platelet and growth factors (Lai et al, 2015). In contrast, DP shows its effect by increasing PDGF levels.…”
Section: Discussionmentioning
confidence: 99%
“…There was no reduction in the release of anabolic growth factors when patients used acetylsalicylic acid or acetylsalicylic acid with clopidogrel [ 37 ]. NSAIDs such diclofenac and meloxicam did not alter the release of VEGF and PDGF-AB levels of PRP [ 38 ]. There was no difference in thrombin production and platelet activation in response to TRAP-6, but there was significantly decreased ADP-induced platelet activation [ 39 ].…”
mentioning
confidence: 99%